Induction of labor at term pregnant women with premature rupture of membranes - Rojas Jaimes, José (2015)
OBJECTIVES.? To evaluate the obstetric and perinatal results in term patients with premature rupture of membranes (PROM) who were submitted for labor induction with oxytocin. MATERIAL AND METHODS.? Retrospective study done at the Arzobispo Loayza Hospital obstetrical service between April 1998 and March 1999 (1year), includes al1 term pregnant women with PROM who had labor induced with oxytocin. RESUL7S 324 patients (8, 1 %) presented PROM, 288 (88,9%) were term pregnancies and 89 fultilled the inclusion criteria. Vaginal delivery occurred in 76 patients (85,6%). Nine patients (10, 1 ?/o) had chorioamniotitis. Only 3 neonates presented Apgar score 4to 6, 10 (11,2%) qualified as potentially infected neonates and 14 (15,7%) presented signs of neonatal sepsis. The final evolution was satisfactory in all cases. CONCLUSIONS.? Induction of labor with oxytocin showed favorable results in 85% of cases, although 15,7% of newborns presented neonatal sepsis.